Virtual Car Editor - HELLQVIST, ALBIN; HUDA, TASDIKUL (My University, 2017)
Volvo Cars is one of the most leading car manufacturer in the world and they produce over several hundreds of thousands cars a year. The cars produced need among other things troubleshooting and diagnostics. This project has been executed in cooperation with Diagnostics & dependability, which is a section within Volvo Cars, responsible for delivering car diagnostics and troubleshooting information to workshops all over the world. In order to troubleshoot the cars, the group develop scripts used to send requests to a test car and log the obtained response. Examples of requests can be the car’s engine’s current revolutions per minute or total distance travelled. The scripts developed can also be tested against a virtual car which in this context is an XML file consisting of a set of requests and responses, corresponding to a car's requests and responses. Managing virtual cars today can be very tedious since it requires that you have to deal with XML-files by hand in order to perform necessary work. This method is not only inefficient but also very time consuming, especially if the content of a XML file is large. To facilitate the working process for Diagnostics & dependability, this project aimed to develop a more efficient method for managing virtual cars. The result of this project is an application developed in Visual Studio using C# as the programming language. This application consists of three main functions that allow a user to generate, merge and modify virtual cars. The application developed is important in the matter that it is no longer required to deal with XML files in the same extension as before.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science